The forgotten fauna: Native vertebrate seed predators on islands. (13th August 2020) - Carpenter, Joanna K.; Wilmshurst, Janet M.; McConkey, Kim R.; Hume, Julian P.; Wotton, Debra M.; Shiels, Aaron B.; Burge, Olivia R.; Drake, Donald R.
Abstract: Human colonization of islands has resulted in the reduction or loss of many native species, and the introduction of non‐native species, producing novel ecosystems. The impacts of these changes on mutualistic plant–animal interactions have received considerable attention, but the potential effects on some antagonistic interactions, such as seed predation, are less thoroughly understood, and often overlooked. Using three archetypal island groups—New Zealand, the Mascarenes and Hawaiʻi—we compare the taxonomic richness and functional diversity of vertebrate seed predators from prehuman and contemporary ecosystems. We scored species on several traits relevant to seed predation, then clustered species into functionally similar groups using hierarchical clustering. These archipelagos once supported between 19 and 24 species of exclusively avian seed predators (representing two to four orders) ranging from large, flightless herbivores to small, volant finches and parrots. Following human arrival, 63%–89% of these species went extinct, and between 12 and 23 non‐native seed predators were introduced. Contemporary seed predator faunas consist of between 14 and 26 species (representing six to seven orders), dominated by non‐native granivorous birds and omnivorous mammals. Our results reveal several examples in which non‐native species may be functionally similar to extinct seed predators, but most non‐native species are functionally different from extinct species, and therefore may be introducing novel seed predation pressures for insular ecosystems. Mammalian seed predators are especially functionally different from the native avian seed predators, as their teeth and widespread habitat distribution allow them to destroy a more diverse range of seeds, including the largest seeds. We highlight the need to understand how these altered seed predator communities are affecting native plant populations, particularly in the context of reduced pollination and seed dispersal. More broadly, we argue that antagonistic interactions are an integral part of any ecosystem, and therefore must be understood if we are to achieve more holistic restoration frameworks for insular ecosystems. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.